Analisis Pengaruh Kemampuan, Usaha dan Dukungan Perusahaan terhadap Kinerja Karyawan pada CV Sandang Gloria Konveksindo - Jerry Logahan; Synthia Atas Sari; Dian Marisa (Bina Nusantara University, 2012)
Clothing Konveksindo CV Gloria is a trading company engaged in the sale of products and clothing items. Therefore, the performance of employees is very important in achieving that goal. The purpose of this study was to analyze the influence of ability, effort, and support the company towards the employee's performance CV Gloria Konveksindo Clothing. The method of analysis used in this study is descriptive, Pearson Regression, and Multiple Regression. Data obtained from the appraisal of employee performance by filling in the questionnaire that has been provided by using a Likert scale that is useful to know the degree of disagreement and agreement existing employees to the question on the questionnaire. The results achieved in this study were the ability of employees to work have an influence for 28.8% of employee performance, employee efforts in working to have the effect of 50.6% on employee performance, corporate support for work processes have the effect of 47.7% the performance of employees, while the ability of employees, employee efforts, and support the company has influence for 66.3% of the employee's performance CV Gloria Konveksindo Clothing. With this capability expected of employees, employee efforts, and support the company serve as the main factor to improve employee performance.